Phytosphingosine ceramide mainly localizes in the central layer of the unique lamellar phase of skin lipid model systems - Andreea Nădăban; Gerrit S. Gooris; Charlotte M. Beddoes; Robert M. Dalgliesh; Joke A. Bouwstra (Journal of Lipid Research, 2022)
Understanding the lipid arrangement within the skin’s outermost layer, the stratum corneum (SC), is important for advancing knowledge on the skin barrier function. The SC lipid matrix consists of ceramides (CERs), cholesterol, and free fatty acids, which form unique crystalline lamellar phases, referred to as the long periodicity phase (LPP) and short periodicity phases. As the SC lipid composition is complex, lipid model systems that mimic the properties of native SC are used to study the SC lipid organization and molecular arrangement. In previous studies, such lipid models were used to determine the molecular organization in the trilayer structure of the LPP unit cell. The aim of this study was to examine the location of CER N-(tetracosanoyl)-phytosphingosine (CER NP) in the unit cell of this lamellar phase and compare its position with CER N-(tetracosanoyl)-sphingosine (CER NS). We selected CER NP as it is the most prevalent CER subclass in the human SC, and its location in the LPP is not known. Our neutron diffraction results demonstrate that the acyl chain of CER NP was positioned in the central part of the trilayer structure, with a fraction also present in the outer layers, the same location as determined for the acyl chain of CER NS. In addition, our Fourier transformed infrared spectroscopy results are in agreement with this molecular arrangement, suggesting a linear arrangement for the CER NS and CER NP. These findings provide more detailed insight into the lipid organization in the SC lipid matrix.